Pengaruh Disiplin Kerja dan Motivasi Intrinsik terhadap Kinerja Karyawan pada PT. XYZ - Amelia Zahra; Syahrial Addin; Yulia Mujiaty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Employee performance plays a crucial role in ensurin the achievement of organizational goals while maintaining the continuity of company operations. Optimal performance reflects the quality of human resources as well as the effectiveness of internal managerial practices. This study aims to analyze the influence of work discipline and intrinsic motivation on employee performance at PT. XYZ. Data were collected through observation and questionnaires, involving 40 employees using a total sampling technique. Data analysis included validity and reliabilityitests, classical assumptionitests, multiple linear regression, partialitests, simultaneous tests, and the coefficient of determination (R²), assisted by SPSS version 27. The results indicate that work discipline (X1) does not significantly affect employee performance, with a significance value of 0.578 > 0.05 and a t-value of 0.561 < 2.026. Meanwhile, intrinsic motivation (X2) has a positive and significant effect on performance, with a significance value of 0.000 < 0.05 and a t-value of 9.004 > 2.026. The F-test yielded a significance value of 0.000 < 0.05 and an F-value of 59.968 > 3.35. These findings highlight the importance of enhancing intrinsic motivation to achieve optimal performance and suggest further research to explore additional variables, providing a foundation for both management and future researchers in developing sustainable, consistent, and comprehensive employee performance strategies.